Actinomycetes as plant growth promoter of rice plants and biocontrol agent against bacterial leaf streak disease - Mohd Hata, Erneeza (2019)
Bacterial leaf streak (BLS) disease caused by Xanthomonas oryzae pv. oryzicola (Xoc) is one of the most important rice bacterial diseases. Genotypic and phenotypic similarity of this pathogen to the causal agent of bacterial leaf blight (BLB), Xanthomonas oryzae pv. oryzae (Xoo), has driven an interest on BLS study. Bacterial leaf streak control measures are focusing on the development of resistant varieties and application of copper-based fungicide. Actinomycetes possess a remarkable potential as biological agent. This study was conducted with the following objectives; 1) to characterize the causal pathogen of BLS disease, Xoc and to differentiate it from other Xanthomonas oryzae pathovar, Xoo, 2) to characterize and determine the potential of actinomycetes as biocontrol agent against Xoc and as plant growth promoter and 3) to evaluate the efficacy of actinomycetes treatment on rice growth promotion and BLS suppression through the induction of defense-related enzymes. Five Xoc isolates were discovered in this study and successfully differentiated with Xoo. BLS symptoms were pronounced during early infection stage, yellow small streak lesions can be observed in rice leaves. Xoc can be detected and differentiated with Xoo by multiplex PCR method. Molecular characterization by gyrase subunit B gene amplification had successfully identified all five isolates as Xanthomonas oryzae pv. oryzicola (accession number in GeneBank database (MH560793-MH560797). All isolates developed hypersensitivity reaction on Nicotiana tabacum. Isolate TKC1 is the most virulent isolate, produced 6.78 cm lesion length in pathogenicity assay compared to other four Xoc isolates. Out of 20 Xoc antagonistic actinomycetes, 60% were belonged to various species of Streptomyces. Rhizospheric actinomycetes, SS8 demonstrated the highest (p≤0.05) antagonistic activity with inhibition value of 17.67 mm, followed by TKSC3 (14.00 mm). Isolate SS8 and TKSC3 were identified as Streptomyces sp SW4-2S and Streptomyces shenzhenensis, respectively by 16s rRNA amplification. Both isolates also possess potentials as hydrolytic enzyme producer and plant growth promoter based on in vitro assessment. In vitro assessment with 12 hours seed bacterization with single or consortium treatment of TKSC3 and SS8 isolates revealed significant (p≤0.05) improvement in rice seed germination and seedling vigor performance. TKSC3 and SS8 were both root colonizing and endophytic streptomycetes with average population ranged from 0.66 to 6.52 x 103 CFU/g in seedling roots at 10 days after seed bacterization treatment. Consortium treatment (TKSC3+SS8) exhibited the highest values in plant growth parameters, total chlorophyl, soil and leaf nutrient contents in glasshouse experiment. Consortium treatment (TKSC3+SS8) also demonstrated the highest BLS disease suppression efficiency at 81.02% with the lowest AUDPC value of 95.79. Single and consortium treatments of actinomycetes successfully suppressed BLS disease by enhancing defense-related enzymes accumulation in the rice plant. Peroxidase, polyphenol oxidase, phenyl ammonia lyase and β,1-3 glucanase enzymes activity were increased in actinomycete-treated plants compared to untreated plants which started at 2 days post inoculation. This study confirmed that actinomycetes possess huge potentials as plant growth promoter and biocontrol agent against Xoc pathogen.